(untitled) (CIPEEX, 2025)
This project focuses on developing a telemedicine platform dedicated to mental health, offering an accessible and practical solution for connecting patients with psychologists and psychiatrists. Designed for mobile devices, the application features session scheduling, emotional assessments using the DASS-21 scale, and video-call consultations. The primary objective is to democratize access to mental health care, removing geographical and economic barriers and modernizing therapeutic monitoring, particularly during critical times. Key development aspects include software usability testing to ensure effectiveness, compliance with the General Data Protection Law (LGPD), and adherence to medical and psychological council guidelines. Additionally, support for trademark registration and the visual identity of the brand will be addressed. The platform employs modern technologies such as React Native for the interface, Node.js and Express for the back-end, and MySQL or PostgreSQL for databases. Following the Minimum Viable Product (MVP) methodology, essential features like patient and professional registration, session scheduling, and emotional assessments will be validated. Upon completion, the platform aims to provide a robust solution for emotional support, significantly improving users’ quality of life and transforming mental health care delivery.